PENGGUNAAN TEPUNG TALAS SEBAGAI SUBSTITUSI TEPUNG TAPIOKA TERHADAP KARAKTERISTIK FISIKOKIMIA DAN ORGANOLEPTIK BAKSO DOMBA (Using of taro flour as a substitute of tapioca flour on physicochemistryl and organoleptic characteristics of lamb meatballs) - Chinta R. L. Nubatonis; Gemini E.M. Malelak; Heri Armadianto; Tri R. Zainal; Pieter Rihi Kale (Universitas Nusa Cendana, 2022)
Lamb meatballs are rarely found in the market, because lamb meat has a distinctive aroma. One way to reduce the distinctive aroma of lamb meatballs is to use various types of flour in combination with tapioca flour. The purpose of this study was to determine the quality of meatballs processed from lamb and given taro flour as a substitute for tapioca flour. A completely randomized design (CRD) 5 x 4 was used in this experiment. The five treatments used were: T0 = no taro flour (control); T25=25% taro flour 25%; T50 = 50% taro flour; T75 = 75% taro flour; T100 = 100% taro flour, and each unit was tested four times. Parameters measured were: pH, water holding capacity (WHC), cooking loss, water and fat content, aroma, color, elasticity and taste. The parametric data was analyzed using ANOVA, while the nonparametric data was analyzed using the Kruskal-Wallis test. The statistical analysis result showed that a balanced mixture of tapioca and taro (50%) caused a decrease in pH (P<0.01). The higher the percentage of taro to substitute tapioca, caused a decrease in WHC and an increase in cooking loss (P<0.05), decreased water content, increased fat content (P<0.01), but did not affect aroma, color, elasticity and taste (P>0.05). The results of this study concluded that the use of taro flour as a substitute for tapioca flour in processing lamb meatballs do not change the organoleptic value of meatballs. Taro flour can be used to replace tapioca flour in processing lamb meatballs as much as 50%.